Gambaran Narsistik pada Remaja dan Implikasi bagi Konseling Kelompok - Ratu Septi Choirunnisa; Evi Afiati; Putri Dian Dia Conia (Journal of Education and Counseling (JECO), 2020)
This study aims to obtain a description of the narcissistic behavior of grade VIII students and to design a group counseling program as an effort to prevent and reduce narcissistic behavior. This type of research is descriptive research. The sampling technique was carried out by using a random sampling technique, with a sample of 181 grade VIII students of SMPN 3 Kota Serang. Research on narcissistic behavior is seen from eight aspects, namely feelings of grandeur and self-interest, filled with fantasy, expressive need to be admired, exploiting interpersonal relationships, lack of empathy, feeling jealous, behaving arrogantly and arrogantly, and feeling special and special individuals . The data collection technique used the distribution of research instruments in the form of questionnaires. While the data analysis technique used is descriptive quantitative. The results showed that the level of narcissistic grade VIII students of SMPN 3 Serang City was in the low category with a percentage of 13%, the medium category with a percentage of 76%, and the high category with a percentage of 11%. After knowing the narcissistic picture, then designing a program is made based on the research results obtaine.